Optimizing students’ motivation through PBL-based worksheets in teaching circles: A classroom action research in Grade 7 - Agung Rivansyah; Agung Deddiliawan Ismail; Ayu Kurniawati (Jurnal Pendidikan Profesi Guru, 2024)
This study employed a classroom action research (CAR) design, conducted in two cycles, each comprising four stages: planning, action, observation, and reflection. The research was carried out in Grade 7 at SMPN 03 Batu. Data were collected through questionnaires, observations, interviews, and documentation. The findings indicate a significant increase in students’ motivation to learn mathematics following the implementation of Problem-Based Learning (PBL)-based student worksheets (LKPD). The percentage of students’ learning motivation exceeded the success indicator, reaching 72%, which falls under the "high" category. This suggests that the integration of PBL into learning materials can effectively foster greater engagement and motivation among students. Therefore, it is recommended that mathematics teachers consider utilizing PBL-based worksheets to make learning more interesting, interactive, and motivating for students.